The Christmas light - VanLiere, Donna, 1966- (St. Martin's Press, 2014)
"In the small town of Grandon, five very different people discover the true meaning of Christmas. Jennifer and Ryan are both single parents, struggling with their own losses and heartache. Sixteen-year-old Kaylee is faced with a life-changing situation that has affected her whole family. Stephen and Lily are happily married and ready to start a family. All of them are facing their own struggles, and all are finding their way through the dark. When they are brought together for a rather unconventional church Nativity, they will learn that with strength, courage, and love, there is always hope. "--